Beneficial behavioral effects of chronic cerebral dopamine neurotrophic factor (CDNF) infusion in the N171-82Q transgenic model of Huntington’s disease - P. Stepanova; D. Kumar; K. Cavonius; J. Korpikoski; J. Sirjala; D. Lindholm; M. H. Voutilainen (Scientific Reports, 2023)
Abstract Huntington’s disease (HD) is a progressive inherited neurological disease characterized by the degeneration of basal ganglia and the accumulation of mutant huntingtin (mHtt) aggregates in specific brain areas. Currently, there is no treatment for halting the progression of HD. Cerebral dopamine neurotrophic factor (CDNF) is a novel endoplasmic reticulum located protein with neurotrophic factor properties that protects and restores dopamine neurons in rodent and non-human primate models of Parkinson’s disease. Our recent study showed that CDNF improves motor coordination and protects NeuN positive cells in a Quinolinic acid toxin rat model of HD. Here we have investigated the effect of chronic intrastriatal CDNF administration on behavior and mHtt aggregates in the N171-82Q mouse model of HD. Data showed that CDNF did not significantly decrease the number of mHtt aggregates in most brain regions studied. Notably, CDNF significantly delayed the onset of symptoms and improved motor coordination in N171-82Q mice. Furthermore, CDNF increased BDNF mRNA level in hippocampus in vivo in the N171-82Q model and BDNF protein level in cultured striatal neurons. Collectively our results indicate that CDNF might be a potential drug candidate for the treatment of HD.